2019
DOI: 10.14309/01.ajg.0000613324.15639.1f
|View full text |Cite
|
Sign up to set email alerts
|

P089 Secukinumab Induced Ulcerative Colitis in a Patient With Psoriatic Arthritis: A Novel Approach to Refractory Cases

Abstract: INTRODUCTION: Secukinumab is an anti-IL 17A monoclonal antibody currently used to treat psoriasis, ankylosing spondylitis, and psoriatic arthritis. It may induce inflammation in the GI tract causing exacerbation of IBD and rarely causing IBD de novo. This phenomenon itself is seldom documented with only a handful of case reports in the US and overseas. The few cases of psoriatic arthritis and Secukinumab- induced UC were managed successfully with infliximab. However, there have been no case reports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A total of 29 studies were identified in the published literature, including 25 case reports ( Ehrlich et al, 2018 ; Grimaux et al, 2018 ; Paul et al, 2018 ; Wang et al, 2018 ; Achufusi et al, 2019 ; Grossberg, 2019 ; Haidari et al, 2019 ; Johnston and Veettil, 2019 ; Philipose et al, 2019 ; Rodriguez et al, 2019 ; Shimizu et al, 2019 ; Smith et al, 2019 ; Darch et al, 2020 ; Fieldhouse et al, 2020 ; Marin et al, 2020 ; Merino Gallego et al, 2020 ; Nazarian et al, 2020 ; Ali et al, 2021 ; Mu et al, 2021 ; Obeidat and Murakami, 2021 ; Ma et al, 2022 ; Sykaras et al, 2022 ; Kukol et al, 2019 ; Nallapeta et al, 2019 ; Sethi et al, 2019 ) and 4 case series ( Fobelo et al, 2018 ; Shukla et al, 2018 ; Vernero et al, 2019 ; Lee et al, 2020 ); a total of 34 cases raised evidence of IBD occurrence during therapy with SEC (27 cases, 79.4%) and IXE (7 cases, 20.6%). Characteristics of the included cases are presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 29 studies were identified in the published literature, including 25 case reports ( Ehrlich et al, 2018 ; Grimaux et al, 2018 ; Paul et al, 2018 ; Wang et al, 2018 ; Achufusi et al, 2019 ; Grossberg, 2019 ; Haidari et al, 2019 ; Johnston and Veettil, 2019 ; Philipose et al, 2019 ; Rodriguez et al, 2019 ; Shimizu et al, 2019 ; Smith et al, 2019 ; Darch et al, 2020 ; Fieldhouse et al, 2020 ; Marin et al, 2020 ; Merino Gallego et al, 2020 ; Nazarian et al, 2020 ; Ali et al, 2021 ; Mu et al, 2021 ; Obeidat and Murakami, 2021 ; Ma et al, 2022 ; Sykaras et al, 2022 ; Kukol et al, 2019 ; Nallapeta et al, 2019 ; Sethi et al, 2019 ) and 4 case series ( Fobelo et al, 2018 ; Shukla et al, 2018 ; Vernero et al, 2019 ; Lee et al, 2020 ); a total of 34 cases raised evidence of IBD occurrence during therapy with SEC (27 cases, 79.4%) and IXE (7 cases, 20.6%). Characteristics of the included cases are presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%